Performance of sustainable concrete made from waste oyster shell powder and blast furnace slag. (15th April 2022) - Han, Yi; Lin, Runsheng; Wang, Xiao-Yong
Abstract: Concrete is the most commonly used building material. While presenting excellent performance, it also has adverse effects on the Earth's climate and ecological environment. This study aims to investigate the viability of waste oyster shell powder (OSP) and industrial by-product blast furnace slag (BFS) as cement replacement alternatives in the preparation of sustainable concrete. The macroscopic performance parameters of the mortar, including the compressive strength, ultrasonic pulse velocity, and electrical resistivity, is tested experimentally, and the hydration and microscopic properties of the paste is investigated. The results reveal that the addition of OSP and BFS reduces the working performance, compressive strength, and cumulative heat of hydration of the mortar. However, the later stage pozzolanic reaction of the BFS significantly increases the compressive strength. Furthermore, the addition of BFS considerably increases the surface resistivity of the mortar. The heat of hydration experimental results show that the addition of OSP accelerates the hydration reaction. However, this acceleration effect is only significant in the first 24 h. Microscopic analysis of X-ray diffraction, attenuated total reflection Fourier transform infrared analysis, thermogravimetric analysis, and scanning electron microscopy reveal a synergistic effect between OSP and BFS, resulting in the formation of monocarboaluminate (Mc) and hemicarboaluminate (Hc). This also contributes to the increase in surface resistivity and compressive strength. Finally, the carbon emissions of the mortar are normalized based on the compressive strength. These findings indicate that OSP and BFS can significantly reduce carbon dioxide emissions per unit strength of mortars. Highlights: Produce sustainable concrete from oyster shell powder (OSP) and slag. Analyze hydration, strength, durability of mortars with microscopic tests. Analyze the microstructure of pastes by XRD, FTIR, TG, and SEM. OSP and slag can effectively reduce normalized CO2 emissions. Slag can reduce normalized CO2 emissions greater than OSP.